Fabrication of edge-curled petals-like covalent organic frameworks and their properties for extracting indole alkaloids from complex biological samples - Fanrong Sun; Ligai Bai; Mingxue Li; Changqing Yu; Haiyan Liu; Xiaoqiang Qiao; Hongyuan Yan (Elsevier, 2022)
In this study, a functionalized covalent-organic framework (COF) was first synthesized using porphyrin as the fabrication unit and showed an edge-curled, petal-like and well-ordered structure. The synthesized COF was then introduced to prepare porous organic polymer monolithic materials (POPMs). Two composite POPM/COF monolithic materials with rod shapes, referred to as sorbent A and sorbent B, were prepared in stainless steel tubes using different monomers. Sorbents A and B exhibited relatively uniform porous structures and enhanced specific surface areas of 153.14 m2/g and 80.01 m2/g, respectively. The prepared composite monoliths were used as in-tube solid-phase extraction (SPE) sorbents combined with HPLC for the on-line extraction and quantitative analytical systems. Indole alkaloids (from Catharanthus roseus G. Don and Uncaria rhynchophylla (Miq.) Miq. Ex Havil.) contained in mouse plasma were extracted and quantitatively analyzed using the online system. The two composite multifunctional monoliths showed excellent clean-up ability for complex biological matrices, as well as superior selectivity for target indole alkaloids. Method validation showed that the RSD values of the repeatability (n=6) were ≤ 3.46%, and the accuracy expressed by the spiked recoveries was in the ranges of 99.38%-100.91% and 96.39%-103.50% for vinca alkaloids and Uncaria alkaloids, respectively. Furthermore, sorbents A and B exhibited strong reusability, with RSD values ≤ 5.32%, which were based on the peak area of the corresponding alkaloids with more than 100 injections. These results indicate that the composite POPM/COF rod-shaped monoliths are promising media as SPE sorbents for extracting trace compounds in complex biological samples.